The effect of an ethnoscience-based e-module on elementary students’ scientific literacy - Arie Widya Murni; Hikmah Luqiyah Kartikasari; Eviyanti Asmaul Kusnah; Muhammad Qasim Ali (EduStream: Jurnal Pendidikan Dasar, 2026)
Scientific literacy has become an urgent priority in contemporary science education due to declining learning outcomes after the COVID-19 pandemic and the growing demand for competency-based reform. At the elementary level, science instruction frequently emphasizes memorization rather than reasoning, inquiry, and contextual application, which may hinder the development of foundational scientific literacy. This study aimed to examine the effect of an ethnoscience-based electronic module on elementary students’ scientific literacy. A quantitative approach with a quasi-experimental pretest-posttest control group design was employed. The participants were 60 fifth-grade students from a public elementary school, selected through cluster sampling and divided into an experimental group and a control group. The experimental group learned through a structured ethnoscience-based electronic module integrating local cultural knowledge with formal scientific concepts, while the control group received conventional instruction. Data were collected using a validated and reliable scientific literacy test and analyzed using descriptive and inferential statistics. The results showed a statistically significant difference between groups, with the experimental group achieving moderate improvement (63%) compared to the low improvement of the control group (16%). The highest gain was found in interpreting data and evidence. These findings indicate that integrating cultural contextualization with structured digital learning design effectively enhances elementary students’ scientific literacy. The study concludes that ethnoscience-based digital learning materials can support literacy-oriented science instruction and strengthen foundational competencies in primary education.